2018
DOI: 10.2478/acb-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids metabolism and degradation is regulated during porcine oviductal epithelial cells (OECs) primary culture in vitro – a signaling pathways activation approach

Abstract: The ovary is part of the reproductive system, possessing very important functions in the reproduction process (ovum and embryo transfer, providing a suitable environment for sperm capacitation, etc.). There are two types of cells in the fallopian tubes: alveolar and secretive cells. These study shows the metabolic processes in pig oviductal epithelial cells associated with the activation of signaling pathways of amino acids metabolism and degradation during long-term in vitro culture. Oviductal epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The Affymetrix procedure was performed as previously described (Kranc et al, 2017(Kranc et al, , 2018a(Kranc et al, , 2018bBryja et al, 2018;Chamier-Gliszczyńska et al, 2018;Stefańska et al, 2018;Nawrocki et al, 2018). cDNA was reverse transcribed from total sample RNA (100 ng) (Ambion Ò WT Expression Kit).…”
Section: Microarray Expression Analysismentioning
confidence: 99%
“…The Affymetrix procedure was performed as previously described (Kranc et al, 2017(Kranc et al, , 2018a(Kranc et al, , 2018bBryja et al, 2018;Chamier-Gliszczyńska et al, 2018;Stefańska et al, 2018;Nawrocki et al, 2018). cDNA was reverse transcribed from total sample RNA (100 ng) (Ambion Ò WT Expression Kit).…”
Section: Microarray Expression Analysismentioning
confidence: 99%
“…Therefore, the goal of the present project is to describe molecular changes in OECs during primary in vitro long-term culture, through employing microarray approach. Previous studies have shown various aspects of OECs' morphological modifications and transcriptomic profile changes during in vitro cultivation [3][4][5]. The emphasis of the present study, is on groups of genes associated with nucleotide/ribonucleotide binding mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The results presented in previous studies are a valuable contribution for better understanding and elucidating many biochemical pathways and morphological/metabolomic factors existing in epithelial oviductal cells. Thus, employing a microarray approach, the molecular level processes identified were angiogenesis and blood vessels development [3], carbohydrates [4] and amino acids [5] metabolism. Furthermore, and plasticity of porcine cells associated with reproduction processes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The method used for OEC harvesting and culture has been described in our previous studies [17][18][19]. Briefly, collected oviducts were washed twice in Dulbecco's phosphate buffered saline (PBS) and sectioned longitudinally.…”
Section: Primary Long-term Cell Culturementioning
confidence: 99%